College of Science Library acquisition process system audit and process improvement - Cruz, Fraymon Joy P. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
In 2011, the CSLIB opened its' doors to the different institutes of the College of Science. Eight institute libraries were established coupled with customization and personalization of services. This changing landscape of library service has brought in a demand driven acquisitions that can no longer be adequately addressed by traditional acquisition practices.